2007
DOI: 10.1536/ihj.48.417
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy With Oral Sildenafil and Beraprost for Pulmonary Arterial Hypertension Associated With CREST Syndrome

Abstract: SUMMARYPulmonary arterial hypertension (PAH) is commonly associated with CREST (Calcinosis, Raynaud phenomenon, Esophageal motility disorders, Sclerodactyly, and Telangiectasia) syndrome. Sildenafil, an oral phosphodiesterase type-5 inhibitor, may offer benefits in the pharmacological management of PAH. However, little is known about the long-term hemodynamic effects of sildenafil, and the potential role of sildenafil in longterm combination with beraprost, an oral prostacyclin analogue, remains unclear. We th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…30 Six studies reported haemodynamics (PAP and/or PVR) as outcomes, all of which demonstrated a beneficial effect with dual therapy. 20,28,29,31,33,36 None of the studies reported quality of life as an outcome. Both randomized trials demonstrated improvement in 6MWD, 37,38 and one trial demonstrated improvement in quality of life and time-to-clinical worsening.…”
Section: Combination Pde-5 Inhibitor and Prostaglandin Analoguesmentioning
confidence: 99%
“…30 Six studies reported haemodynamics (PAP and/or PVR) as outcomes, all of which demonstrated a beneficial effect with dual therapy. 20,28,29,31,33,36 None of the studies reported quality of life as an outcome. Both randomized trials demonstrated improvement in 6MWD, 37,38 and one trial demonstrated improvement in quality of life and time-to-clinical worsening.…”
Section: Combination Pde-5 Inhibitor and Prostaglandin Analoguesmentioning
confidence: 99%
“…Because combined therapy of BPS and sildenafil has recently been reported as effective in ameliorating PAH in rats 21 and patients, 22 these drugs may inhibit the development of pulmonary hypertension additively and synergistically. Furthermore, in a patient with PAH secondary to collagen disease combination therapy with BPS and sildenafil was efficacious, 23 and may be also effective in such patients with secondary PAH.…”
Section: Discussionmentioning
confidence: 99%
“…PAH associated with CVD is most commonly observed in systemic sclerosis, mixed connective tissue disease (Figure 3). This patient group is related to interstitial fibrosis, which is most commonly manifested histologically as nonspecific interstitial pneumonia [11], pulmonary vascular disease, or both. A study of PH in 722 patients with systemic sclerosis in the United Kingdom showed a prevalence of approximately 12%, and more than 10% of patients with severe PAH have an associated connective tissue disease, such as mixed connective tissue disease, polymyositis, dermatomyositis, and systemic lupus erythematosus [12].…”
Section: The Comparison Of the Radiologic Findings Between The Idiopa...mentioning
confidence: 99%